Congenital Coronary Artery Anomalies and Implications. Issue 5 (September 2018) - Azour, Lea; Jacobi, Adam H.; Alpert, Jeffrey B.; Uppu, Santosh; Latson, Larry; Mason, Derek; Cham, Matthew D.
Abstract : This pictorial essay presents cases of congenital coronary artery anomalies, including congenital anomalies of origin, course, and termination. Familiarity with atypical coronary anatomy and clinical presentation may facilitate appropriate diagnosis and management, particularly as cardiac and thoracic computed tomographic utilization increases. Abstract : Supplemental Digital Content is available in the text.